A study about urinary tract infection among patients attending tertiary care hospital - U., Arunachalam; C., Ponmudi; Solanke, Prashant V.; Das, Deepam; N., Vignesh; Pawade, Preeti (International Surgery Journal, 2017)
Background: UTI is a second most common type of infection, accounting for nearly 25% of all infections. Lower UTIs are much more common in women than in men, particularly in the under 50’s. UTI are common among patients with type 2 diabetes mellitus. Recurrent UTI is a common phenomenon that is observed among women who have experienced uncomplicated UTIs. Usually 5-10 days of antibiotic therapy is done for treating UTI. Successful antimicrobial therapy will usually ameliorate symptoms promptly, with substantial clinical improvement in 48 to 72 hours. The objective is to find out the knowledge and practice about UTI among UTI sufferers. Methods: The study design is cross sectional study. The study period is from July 2016 to February 2017. The study place is Sree Mookambika Institute of Medical Sciences. The sample size is (4PQ/d²) = 31. Systematic random sampling techniques are used. Institutional ethical committee clearance was obtained. Results: In the study 90.3% are women. In the study 32.3% had a recurrent UTI. In the study population about 51.7% take adequate or plenty of water. In this study 35.5% have poor knowledge, 42% have moderate knowledge and 19.5% have a good knowledge about UTI. Conclusions: From the study, it is learnt that UTI is common among the women and recurrence is the most common thing among the asymptomatic UTI group. The common symptom experienced by the study group is dysuria and frequency and most in the study group used to take less than recommended amount of water daily. They believe drinking plenty of water and cleanliness can prevent the UTI. The knowledge about UTI among the group is fairly good.